Two Cases of Hepatoblastoma in Adults - Elouarith Ihssan; Elagouri Hajar; Bekarsabein Salma; Ech-Charif Soumaya; Mahdi Youssef; Khmou Mouna; El Khannoussi Basma (SAGE Publishing, 2022)
Adult hepatoblastoma is a rare tumor whose etiology and mechanisms of development are still incompletely understood. Imaging and biological tests such as AFP and liver enzymes are non-specific. Histologically, there are 2 histological variants: pure epithelial with 5 types (pure fetal, embryonal, small cell undifferentiated, cholangioblastic, and macrotrabecular), a mixed epithelial and a mesenchymal variant with or without a teratoid contingent. The main differential diagnosis concerns hepatocellular carcinoma. The treatment of hepatoblastoma in adults is not yet standardized and surgery remains the mainstay of treatment. In this report we aim to describe the clinical, pathological, and immunohistochemical features of this rare entity in adult patients and discuss the elements allowing its distinction from hepatocellular carcinoma (HCC).